THE INFLUENCE OF DIGITAL MARKETING AND PRODUCT QUALITY ON TIMES FLORIST PURCHASE DECISIONS IN PALU CITY - Ni Luh Dita Yanti; Ira Nuriya Santi; Maskuri Sutomo; Farid (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the effect of Digital Marketing and Product Quality on Purchasing Decisions at Times Florist in Palu City. The study used a quantitative method with data collection techniques through questionnaires distributed to 90 respondents using purposive sampling. Data were processed and analyzed using the SPSS.26 application through validity tests, reliability tests, classical assumption tests, multiple linear regression, F tests, t tests, and coefficients of determination. The results showed that Digital Marketing had a significant effect on Purchasing Decisions. Product Quality also had a significant effect on Purchasing Decisions. Simultaneously, both variables had a significant effect and were able to explain 85.1% of the variation in purchasing decisions. These findings confirm that optimizing digital marketing strategies and improving product quality are very important to improve consumer purchasing decisions.